A concept for building more humanlike social robots and their ethical consequence - Kirandziska, Vesna; Ackovska, Nevena (My University, 2014)
Human – computer interaction is a vast area of research that targets two very different groups of subjects: the humans as a biology originated group, and the machines – as human made products. One specific part of this interaction is the human – robot interaction. This paper discusses the challenges that arise in the human – robot interaction. Special accent is put on creating social robots, in particular on creating more human-like empathic robots. Here a concept for creating such robots is proposed, where data from human-human interaction is used for feature selection. As an example of the stated concept a robot has been added the ability to perceive human emotions. In this research the robot uses human sound data as source for perceiving human emotions. Additionally, a biologically driven custom algorithm is used in this research for emotion evaluation classification. The proposed approach is analyzed and evaluated using experimental results done from real data. Also, the influence of the emotion aware robots on humans is explained in more detail. At the end, a discussion about the importance of sharing life with these emotion aware robots today and in the future is argued.
Keywords: human-robot interaction, social robots, robotics, emotion classification